What is a “sense of foreshortened future?” A phenomenological study of trauma, trust, and time - Ratcliffe, Matthew; Ruddell, Mark; Smith, Benedict (Frontiers in Psychology, 2014)
One of the symptoms of trauma is said to be a ‘sense of foreshortened future’. Without further qualification, it is not clear how to interpret this. In this paper, we offer a phenomenological account of what the experience consists of. To do so, we focus on the effects of torture. We describe how traumatic events, especially those that are deliberately inflicted by other people, can lead to a loss of what might be termed ‘trust’ or ‘confidence’ in the world. This undermines the intelligibility of one’s projects, cares and commitments, in a way that amounts to a change in the structure of temporal experience. The paper concludes by briefly addressing the implications of this for how we respond to trauma, as well as offering some remarks on the relationship between trauma and psychosis.